Analisis Bibliometrik terhadap Guru Matematika Indonesia Berbasis VOS Viewer - Fadilla, Nadia Nur; Zulfah, Zulfah; Astuti, Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to determine the research trends of Indonesian Mathematics Teachers using bibliometric analysis methods. The data in this study were obtained through Google Scholar from 2013-2023 with the keywords Indonesian math teachers. Researchers analyzed 1000 original articles from 2013-2023. Researchers utilize the use of Publish or Perish software and VOS Viewer to analyze data